Not Singing in the Rain: Linking Migratory Songbird Declines With Increasing Precipitation and Brood Parasitism Vulnerability - Rosamond, Kristen M.; Goded, Sandra; Soultan, Alaaeldin; Kaplan, Rachel H.; Glass, Alex; Kim, Daniel H.; Arcilla, Nico (Frontiers in Ecology and Evolution, 2020)
Few empirical studies have quantified relationships between changing weather and grassland breeding birds, but such studies are vital in a time of rapid climate change. Weather has critical consequences for avian breeding ecology, geographic ranges, and migration phenology. Changing precipitation and temperature patterns affect avian habitat, food resources, and other factors critical to avian life history strategies, and may disproportionately affect species restricted to rare or declining ecosystems, such as temperate grasslands, which are among the most altered and endangered ecosystems globally. We examined the influence of weather on the dickcissel (Spiza americana), a migratory songbird of conservation concern that breeds in temperate grasslands. Our study area in the Platte River Valley, North American Great Plains, featured high historic weather variability, and climate change is now driving higher precipitation and temperatures as well as higher frequencies of extreme weather events including flooding and droughts. Dickcissels share their breeding grounds with brown-headed cowbirds (Molothrus ater), brood parasites that lay their eggs in the nests of other songbirds, reducing dickcissel productivity. We used nine years of capture-recapture data collected over an 18-year period to test the hypothesis that increasing precipitation on dickcissels’ riparian breeding grounds is associated with abundance declines and increasing vulnerability to cowbird parasitism. Dickcissels declined significantly with increasing June precipitation, whereas cowbirds, by contrast, increased. Dickcissel productivity appeared to be extremely low, with a 3:1 ratio of breeding male to female dickcissels likely undermining reproductive success. Our findings suggest that continuing increased precipitation predicted by climate change models in this region may drive future declines of dickcissels and other songbird populations in in the future. Drivers of these declines may include habitat and food resource loss related to flooding and higher frequency precipitation events as well as increased parasitism pressure by cowbirds, whose abundance increases with increasing precipitation. Positive correlations of June-July precipitation, temperature, and time since grazing on dickcissel productivity did not mitigate dickcissels’ declining trend in this ecosystem. These findings highlight the importance of empirical research on weather and brood parasitism vulnerability to inform adaptive management for migratory songbird conservation under climate change.